Analysis of Subgingival Plaque Ability to Stimulate Toll‐Like Receptor 2 and 4. Issue 9 (1st September 2016) - Ziauddin, S.M.; Montenegro Raudales, Jorge Luis; Sato, Kayo; Yoshioka, Hidenobu; Ozaki, Yukio; Kaneko, Takashi; Yoshimura, Atsutoshi; Hara, Yoshitaka
Abstract : Background: It has been shown that toll‐like receptor (TLR) 2‐ and TLR4‐stimulating abilities of supragingival plaque (SPP) are associated with periodontal conditions. It is hypothesized that SPP might affect the periodontium through its influence on subgingival plaque (SBP). This study investigates relationships between TLR2‐ and TLR4‐stimulating abilities of SBP and periodontal conditions. Methods: One hundred thirteen SBP samples were collected from the deepest pockets in patients with chronic periodontitis. TLR2‐ and TLR4‐stimulating abilities were measured using genetically engineered nuclear factor‐kappa B reporter cells. Numbers of Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans in each plaque sample were determined by real‐time polymerase chain reaction. Peripheral blood mononuclear cells (PBMCs) were stimulated with SBP samples in presence or absence of TLR4 or TLR2 inhibitor. Production of tumor necrosis factor (TNF)‐α and interleukin (IL)‐8 was analyzed by enzyme‐linked immunosorbent assay. Results: TLR4‐stimulating ability of SBP was associated with plaque index (PI), but not with other clinical parameters at sampling sites. TLR2‐stimulating ability of SBP was associated with none of the parameters. Number of P. gingivalis and A. actinomycetemcomitans in each plaque sample was not associated with TLR2‐ or TLR4‐stimulating ability of SBP. PBMCs stimulated with SBP samples produced TNF‐α and IL‐8, which was inhibited by TLR4 but not by TLR2 inhibitor. Conclusion: TLR4‐ but not TLR2‐stimulating ability of SBP is associated with PI. Enhanced TLR4‐stimulating ability at sites with accumulated plaque may mediate gingival inflammation.